Conservation and threatened status of plant species with extremely small populations in the karst region of southeastern Yunnan, China - Liu, Yang; Tan, Yu-Lin; Li, Yun-Meng; Ping, Yan-Mei; He, De-Ming; Zhang, Gui-Liang; Sun, Wei-Bang; Cai, Lei (Frontiers in Plant Science, 2024)
The southeastern Yunnan is one of the most typical areas in China with karst landforms. The rich variety of vegetation types and plant diversity means that threatened status are also synchronized. Over the past 20 years, the comprehensive conservation team for plant species with extremely small populations (PSESP) has conducted in-depth field surveys in the region, combining relevant literature and conservation projects to compile a list of PSESP which including conservation and endangered status, conservation actions, and scientific research. Among all 116 PSESP, relatively abundant families include Cycadaceae (12 species), Magnoliaceae (17species) and Orchidaceae (18 species). Hekou and Malipo are the counties with the highest number, with 44 and 43 species respectively. A total of 81 species are included in the List of National Key Protected Wild Plants in China. For threatened status, 24 critically endangered (CR) species and 41 endangered (EN) species represent levels of severe threat. Up to now, 96 species have taken at least one protective measure from in situ conservation, ex situ conservation, breeding or reintroduction/reinforcement. But there are still 20 species that have not taken any protective measures. Additionally, scientific research has been conducted on 86 species, but 30 species have not had any research initiated. The threat of human interference mainly including overcollection and habitat destruction, and the threats of limitations imposed on PSESP itself and natural disasters cannot be ignored. Our findings underscore the importance of integrated conservation strategies, in addition to the in situ conservation, ex situ conservation, breeding or reintroduction/reinforcement, we should also pay attention to the scientific research, germplasm conservation, environmental education and ethnic culture. We also propose to consider establishing a professional karst botanical garden in southeastern Yunnan, and hope this study can offer valuable insights for the conservation of PSESP and biodiversity in southeastern Yunnan.